Enhancing the bioactivity of polymeric implants by means of cold gas spray coatings. Issue 7 (6th March 2014) - Gardon, M.; Melero, H.; Garcia‐Giralt, N.; Dosta, S.; Cano, I. G.; Guilemany, J. M.
Abstract Nanostructured anatase coatings were built‐up on biocompatible polyetheretherketone (PEEK) by means of cold gas spray (CGS). Titanium layer was previously desposited, which acted as bond coat between PEEK and metal oxide. Semicrystalline polymer was not degraded during the spraying process and starting composition of titanium dioxide was not affected. TiO2 was homogeneously obtained onto CGS Ti layer and completely covered the piece. Primary human osteoblasts were seeded onto biomaterials and in vitro cell experiments provided evidence to confirm that nanostructured anatase coatings deposited by cold gas spray improve the performance of PEEK implants. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 1537–1543, 2014.